Intermittent neurologic decompensation: An underrecognized presentation of tyrosine hydroxylase deficiency - Marjolaine Champagne; Gabriella A. Horvath; Sébastien Perreault; Julie Gauthier; Keith Hyland; Jean‐François Soucy; Grant A. Mitchell (JIMD Reports, 2022)
Abstract Tyrosine hydroxylase deficiency (THD) is a treatable inborn error of dopamine biosynthesis caused by mutations in TH. Two presentations are described. Type A, milder, presents after 12 months of age with progressive hypokinesis and rigidity. Type B presents before 12 months as a progressive complex encephalopathy. We report a girl with mild THD who had recurrent episodes of neurological decompensations. Before the first episode, she had normal development except for mild head tremor. Episodes occurred at 12, 19, and 25 months of age. After viral infections or vaccination, she developed lethargy, worsened tremor, language, and motor regression including severe axial hypotonia, recuperating over several weeks of intensive rehabilitation but with residual tremor and mild lower limb spasticity. Basal ganglia imaging was normal. Exome sequencing revealed two missense variants of uncertain significance in TH: c.1147G>T and c.1084G>A. Both have low gnomAD allele frequencies and in silico, are predicted to be deleterious. Cerebrospinal fluid analysis showed low homovanillic acid (HVA, 160 nmol/L, reference 233–938) and low HVA/5‐hydroxyindolacetic acid molar ratio (1.07, reference .5–3.5). She responded rapidly to L‐Dopa/carbidopa without further episodes. Literature review revealed four other THD patients who had a total of seven episodes of marked hypotonia and motor regression following infections, occurring between ages 12 months and 6 years. All improved with L‐Dopa/carbidopa treatment. Intermittent THD is treatable, important for genetic counseling, and should be considered after even a single episode of marked hypotonia with recuperation over weeks, especially in patients with preexisting tremor, dystonia, or rigidity.